The arbitration (amendment) act 2011: limiting court intervention in arbitral proceedings in Malaysia - Idid, Syed Ahmad; Oseni, Umar Aimhanosi (LexisNexis, 2014)
It seems obvious and trite that court intervention in arbitral proceedings has continued to generate controversy among practitioners and researchers. Through a series of amendments to comply with international best practices in the field of arbitration, Malaysia has again introduced another phase in the practice of arbitration. This is part of the continuous drive towards a substantial compliance with the UNCITRAL Model Law on International Commercial Arbitration of 1985 (as revised in 2006). The Arbitration (Amendment) Act 2011 amends certain provisions of the Principal Act (Arbitration Act 2005). This paper examines the major highlights of the new amendments with particular focus to the extent of curial intervention in the arbitral process. The paper concludes that though the jurisdiction or intervention of the court cannot be totally ousted, it can however be limited to benign judicial regulation, as shown in this salutary amendment of the Arbitration Act 2005. Such clear and unambiguous amendments are necessary to smoothen, facilitate and streamline the arbitral process to make it more accessible to parties.